The Influence of Regional Original Income, Capital Expenditure and Employee Expenditure on the Level of Regional Financial Independence in Regencies/Cities in East Java Province in 2020-2023 - Sindy Utami; Maulidah Narastri (International Journal of Economics, Management and Accounting, 2025)
The purpose of this study was to analyze the effect of local revenue, capital expenditure and employee expenditure on the level of financial independence of districts / cities in East Java Province in the period 2020-2023. The research was conducted using a quantitative approach using secondary data in the form of regional revenue and expenditure budget realization reports obtained through the official website of the Directorate General of Fiscal Balance. A total of 38 districts / cities in East Java Province in 2020-2023 were selected as the population in this study. Saturated sampling was used as a sampling method, so that a sample of 152 samples was obtained. The results showed that local revenue and regional employee expenditure partially had a significant effect on the level of regional financial independence, while capital expenditure had no significant effect on the level of regional financial independence. Meanwhile, local revenue, capital expenditure, and employee expenditure together have a significant effect on the level of regional financial independence